Treatment of Domestic Wastewater with Fixed Bed Biofilm Reactor - Hayder, Gasim; Perumulselum, Puniyarasen; Alhussian, Hitham (International Journal of Engineering and Technology, 2018)
Fixed bed biofilm reactors were evaluated with three different arrangements of bio-balls. The performance of different arrangements was evaluated based on chemical oxygen demand (COD), total suspended solid (TSS) and mixed liquor suspended solid (MLSS). The three rectors were fabricated and operated in lab scale model with real domestic wastewater. Considering the TSS removal efficiency, arrangement one was the best followed by arrangement two and arrangement three. While for COD, arrangement one recorded the highest removal efficiency followed by arrangement two and column. The average COD concentration for arrangement one was 23 while for arrangement two and arrangement three was 25 and 36 mg/l respectively. The overall average effluent TSS concentrations for the arrangement one, two and three were 25, 32 and 45 mg/l respectively. TSS and COD removal was almost the same for arrangement one and arrangement two but arrangement one has the highest among them, and all removal is acceptable under Malaysian standards. Besides that, all the three arrangements have the differences in terms of maintenance and installation. There was no clogging occurred in all the three arrangements.